2015
DOI: 10.1007/s00238-015-1094-1
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive strategies for enhancing language development in children with cleft palate

Abstract: Background Children born with cleft palate frequently show compensatory articulation errors (CA), and they are also at risk for language delays. There is a need of studies on speech-language intervention in this patient group. The purpose of this paper is to study metacognitive strategies for enhancing language development in children with cleft palate. Methods Twenty-six children with unilateral cleft lip and palate (UCLP) were studied and divided in two groups. The age of the patients ranged from 5 to 8 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(40 reference statements)
2
8
0
Order By: Relevance
“…Through the use of metacognitive strategies, children become more able to incorporate details in their narrations and they can take different perspectives when analyzing the plot of a story. Thus, it may be concluded that metacognitive strategies can be useful for enhancing higher-order language for narration, interpretation, evaluation and organization, and this could be reflected in both, written and oral language [24]. This conclusion agrees with The Local Homology Model described by Bates, et al, which argues that language is an interactive system that depends crucially on processes and representations from a variety of cognitive domains [29].…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Through the use of metacognitive strategies, children become more able to incorporate details in their narrations and they can take different perspectives when analyzing the plot of a story. Thus, it may be concluded that metacognitive strategies can be useful for enhancing higher-order language for narration, interpretation, evaluation and organization, and this could be reflected in both, written and oral language [24]. This conclusion agrees with The Local Homology Model described by Bates, et al, which argues that language is an interactive system that depends crucially on processes and representations from a variety of cognitive domains [29].…”
Section: Resultssupporting
confidence: 78%
“…Many of them are developed naturally. However, it is now recommended that they should be explicitly taught during stimulation or intervention [24]. It has been described that expert readers use the strategies described herein for making meaning from text [27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations